Effectiveness of a commercial head-neck cooling device - Bulbulian, R.; Shapiro, R.; Murphy, M.; Levenhagen, D. (The Journal of Strength and Conditioning Research, 1999)
The effects of head and neck cooling (Kool-It) on selected cardiovascular, thermoregulatory, and perceptual variables were studied in 10 men and 10 women tested during 30 minutes of exercise on a cycle ergometer at 60% maximum oxygen consumption (o2max) under control (C; 30° C) and experimental head and neck cooling (E) conditions. The data show no significant (C vs. E group) differences in postexercise core temperature measured rectally or esophageally (38.1 ± 0.02 vs. 38.2 ± 0.03 and 37.9± 0.04 vs. 37.9 ± 0.04° C, respectively). Systolic and diastolic blood pressure showed no change after exercise (172 ± 1 vs. 171 ± 2 and 62 ± 1 vs. 64 ± 1 mm Hg, respectively). Heart rate, oxygen consumption per unit time, rating of perceived exertion (RPE), and mean skin temperatures also showed no significant differences between conditions. Thigh and calf skin temperature (Tsk) increases were greater in women than men (p < 0.05). Sweat rate was greater for women in the E than the C condition (697 ± 71 vs. 657 ± 67 g·h1; p < 0.05), whereas plasma volume shift was significantly greater in men during E condition (7.8 ± 1.6 vs. +0.5 ± 2.5%; p < 0.02). Finally, a significant RPE slope by sex-by-treatment interaction (p < 0.0004) showed a lower RPE slope response to exercise for women in the C condition. The data are interpreted to refute claims regarding the benefits of neck and head cooling during exercise from the Kool-It device, although some regional Tsk sex differences were observed. Kool-It had no effect on RPE during exercise in men, but accelerated RPE increases in women.